O discurso da imprensa escrita recifense nas notícias de violência contra a mulher nos casos de "legítima defesa da honra" - Silva, Luciana Pereira da (2009)
The purpose of this study was to identify, in the discourse of the written press of Recife, the image of women in the reporting of violence suffered by than in cases of legitimate defense of honor . The news as a social practice commits the professionals in involved in the production and dissemination of the news in the construction of the image of women. The corpus, consisting of ten news items, is analyzed in the tree-dimensional framework of Critical Discourse Analysis (CDA. This takes as its starting point the participle that the discourse of the press is not a neutral on; the categories of analysis are ethos, intertextuality and interdiscursivity and ideology, representing fundamental phenomena in identifying the way in which the written press constructs the image of a woman. The findings of the study revealed that in such discourse the image of a woman so constructed is that in which she is the one to blame‟ for the violence for having provoked such an act by her behavior or attitude